Experimental cryptococcosis in normal and B-cell-deficient mice. - Monga, D P (1979)
B-cell-deficient mice were prepared by administration of rabbit anti-mouse-mu antiserum to newborn animals within 12 h of birth onwards. Such immunodeficient animals, along with the normal controls, were infected intravenously with Cryptococcus neoformans. There was no difference in the mortality pattern, viable count of cryptococci in different organs, delayed-type hypersensitivity reaction, and antigen level in the sera of control and B-cell-deficient animals. Antibodies were absent in B-cell-deficient animals but were present in low titers in control animals. It is concluded that antibodies are not involved in protection of mice infected with C. neoformans.